2014
DOI: 10.1063/1.4879547
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics simulation of electrokinetic flow of an aqueous electrolyte solution in nanochannels

Abstract: Electrokinetic flows of an aqueous NaCl solution in nanochannels with negatively charged surfaces are studied using molecular dynamics (MD) simulations. The four transport coefficients that characterize the response to weak electric and pressure fields, namely the coefficients for the electrical current in response to the electric field

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
65
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(67 citation statements)
references
References 49 publications
2
65
0
Order By: Relevance
“…Both these quantitative conclusions of our free energy model calculations, in the condensation approach, are in agreement with the reported experimental data indicating stability near the isoelectric point, driven by the release of counterions during the formation of the lamellar complex. This latter important contribution has been calculated in the most demanding critical contribution typical of the condensation theory, which is in agreement with the most demanding experiments on the confinement of condensed counterions, and also supported by very recent dynamical data from a simulation in planar geometry …”
Section: Discussion and Summarysupporting
confidence: 85%
“…Both these quantitative conclusions of our free energy model calculations, in the condensation approach, are in agreement with the reported experimental data indicating stability near the isoelectric point, driven by the release of counterions during the formation of the lamellar complex. This latter important contribution has been calculated in the most demanding critical contribution typical of the condensation theory, which is in agreement with the most demanding experiments on the confinement of condensed counterions, and also supported by very recent dynamical data from a simulation in planar geometry …”
Section: Discussion and Summarysupporting
confidence: 85%
“…cluding electro-or thermo-osmosis flows 26,27 -, is that it is a force-free transport phenomenon. This can be demonstrated from the fact that the hydrodynamic velocity profile is flat far away from the surface, so that all forces acting on the surface -direct interactions and hydrodynamics -do vanish in the bulk.…”
Section: B Principles For An Nemd Diffusio-osmosismentioning
confidence: 99%
“…Note that the large electric fields considered here are commonly used in MD studies to extract the induced fluxes from thermal noise [42,43,[49][50][51][52][53]; indeed, it has been shown that electrokinetic response coefficients obtained with such electric fields were consistent with equilibrium results obtained through the linear response theory, i.e., in the limit of vanishing forcing [50,54,55].…”
mentioning
confidence: 58%